Targeting Contrast Agents With Peak Near-Infrared-II (NIR-II) Fluorescence Emission for Non-invasive Real-Time Direct Visualization of Thrombosis - Hettie, Kenneth S. (Frontiers in Molecular Biosciences, 2021)
Thrombosis arises when pathological factors compromise normal haemostasis. Arterial (AT) and venous (VT) thrombosis lead to life-threatening cardio-cerebrovascular complications. The therapeutic window following AT and VT onset is insufficient for treatment. Acute AT is the cause of heart attacks and most stroke incidences, while acute VT leads to fatal therapy complications. Early lesion detection, identification, and treatment of thrombi can abate adverse events. Fresh thrombi therapy success rate is higher than that of old thrombi, and thus detection of the former and discernment of lesions are of paramount importance. Magnetic resonance imaging, X-ray computed tomography, and ultrasound are the imaging modalities used for detecting AT and VT, but such suffer from affording only image-delayed indirect visualization of only late stages of thrombi development. To overcome such limitations, near-infrared (NIR, 700-1700 nm) fluorescence (NIRF) imaging has been implemented to afford noninvasive real-time direct visualization of biological processes. Contrast agents affording real-time direct or indirect visualization of thrombi via using NIRF imaging provide peak NIR-I fluorescence emission ( 700-1000 nm), which affords limited penetration depth and suboptimal resolution. Contrast agents with peak NIR-II fluorescence emission ( 1000-1700 nm) is under development to provide direct visualization of smaller, fresh, and/or deep-seated thrombi. However, peak NIR-II fluorescence-emitting contrast agents that purport to provide direct visualization of thrombi actually afford indirect visualization of such. These contrast agents do not target thrombi/occlusions. This mini review summarizes the targeting contrast agents having peak NIR-II fluorescence emission for noninvasive real-time direct visualization of thrombosis that have been recently reported.